Profil HBA1C pada Pasien Diabetes Melitus Tipe II di Rumah Sehat Baznas Jakarta Tahun 2021 - Martina, Martina; Septian, Farid; Fadhil, Ahmad; Nur A, Siti; Hanafi, Aprizal Satria (JURNAL WACANA KESEHATAN, 2024)
Diabetes mellitus (DM) is a metabolic disease caused by impaired insulin action. The incidence of this disease is still increasing in Indonesia, especially type II DM. Measuring glycated hemoglobin (HbA1c) is the best glycemic control to determine blood glucose levels. Patients who have HbA1c levels >7% are at 2 times higher risk of experiencing complications. Checking HbA1c levels is very important to help establish the diagnosis, glycemic control and prognosis of type II DM. The aim of this study was to determine the description of HbA1c levels in type II diabetes mellitus patients at the Central BAZNAS Health Center in 2021 and the proportions based on region, age and type of therapy. This research uses a cross-sectional descriptive research type. The research sample included an affordable population that met the inclusion and exclusion criteria of 64 samples. The research data is in the form of secondary data obtained from the Hypertension Diabetes program from 2020. Most of the respondents were women (82.8%) and were in the age range of 51-60 years (37.5%) and the least were in the productive age, namely 30-40 year around 4.7%. Respondents who had taken diabetes mellitus medication after having an Hba1C examination showed that the majority (14 people) had normal HbA1C values <6.5% and continued (13 people) with results in the range of 8.7-9.6%. Bogor Regency and Bekasi City, the area with the most respondents is Bogor Regency because there are 2 assisted village points, namely in Ciampea District and Citayam Village, Bojonggede District